2022
DOI: 10.1111/den.14423
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle biopsy with 19G needle is effective in combination with endoscopic ultrasound‐guided tissue acquisition for genomic profiling of unresectable pancreatic cancer

Abstract: Objectives: Comprehensive genomic profiling (CGP) has been approved in Japan since June 2019, enabling mutation-specific therapy. Although tissue sampling via endoscopic ultrasoundguided tissue acquisition (EUS-TA) is standard in pancreatic cancer, reports on obtaining appropriate samples for CGP, especially for the OncoGuide NCC Oncopanel System (NOP) and FoundationOne CDx (FOne), are lacking. Therefore, we investigated the success rate and factors related to appropriate EUS-TA sampling for CGP analysis suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…The frequency of mutations identified in this study is consistent with previous PC studies, with KRAS , TP53 , CDKN2A , and SMAD4 recorded as the most commonly mutated genes [ 5 , 9 , 35 ]. Using a customized gene panel of 28 cancer-related genes, genomic profiles were successfully generated from 26 of 30 patient samples (86.7%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The frequency of mutations identified in this study is consistent with previous PC studies, with KRAS , TP53 , CDKN2A , and SMAD4 recorded as the most commonly mutated genes [ 5 , 9 , 35 ]. Using a customized gene panel of 28 cancer-related genes, genomic profiles were successfully generated from 26 of 30 patient samples (86.7%).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have demonstrated NOP analysis suitability criteria for EUS-FNB using a 19-guage needle for patients with unresectable PC [ 22 , 35 ]. Moreover, one prospective and two retrospective studies have reported on comprehensive genomic testing using 22-guage FNB needles [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 10 the authors concluded that 19G and FNB needles are suitable for CGP analysis, but also that larger needles require a higher degree of skill for puncture and that the complication rate is concerning, although it did not reach the level of significant difference. Moreover, as 22G FNB needles are currently the most commonly used needle type in the real‐world setting, further investigation is warranted in terms of appropriate puncture number, puncture method, and ingenuity in obtaining formalin‐fixed paraffin‐embedded samples.…”
mentioning
confidence: 46%
“…In this issue of Digestive Endoscopy , Ikeda et al 10 . performed a retrospective study assessing the CGP criteria suitability using EUS‐TA samples in a larger number of patients ( n = 150) than the previous reports.…”
mentioning
confidence: 99%
“…Ikeda et al [ 48 ] retrospectively investigated the percentage of cases achieving NCCOP analysis criteria (153 cases in total; FNB 19-G needle: 75 cases, FNB 22-G needle: 43 cases, and FNA 22-G needle: 35 cases). Overall, only 39.0% (60/153) of cases met the NCCOP analysis criteria.…”
Section: Tips For Improving the Success Rate Of Cgp Analysis With Eus...mentioning
confidence: 99%